Mahasiswa dan Junk food (Studi pada Mahasiswa Perantau di Kota Makassar) - Mauliadi Ramli . (PREDESTINASI, 2022)
ABSTRACTThe general objective of this study is to determine the consumption behavior of instant noodles among overseas students at the of Makassar. The specific objectives are to determine the level of knowledge about the consumption of junk food in students, to know attitudes towards consumption of junk food in students, and to know the actions of consuming junk food in students and the health effects due to consuming junk food. This research method uses qualitative methods, namely by observation and interviews. The results showed that to find out the level of knowledge of overseas students about junk food and what is the background for choosing to consume junk food and the impact of junk food on health. The main finding of this study is the background factors for overseas students choosing junk food, namely busyness and busy schedules so that junk food is a mainstay menu to prop up the stomach when hungry.Â Â Â